COMMUNICATION OF THAI PUAN ETHNIC IDENTITY THROUGH COMMUNTY PRODUCT AND PACKAGING OF PAKPLEE DISTRICT, NAKHON NAYOK PROVINCE ACCORDING TO THE KING’S PHILOSOPHY - Wiriyawit, Nathanan (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
The cultural identity of Thai Puan people, Pakplee District, Nakhon Nayok Province Inherited through traditional woven patterns for a long time by blending of religious beliefs and community culture. The Thai Puan community has established a Thai Puan weaving handicraft group at Ban Mai Temple since 2002 but the social changing made the woven fabrics which had high value and lacked of directional promotion from government was in the state of decline in popularity. Therefore, in order to maintain the cultural values, it was necessary to create a community product that could actually be used in daily life by converted the cultural capital to be concrete and created added value for the community product and packaging. That was starting point of the study of Communication of Thai Puan Identity through Community Product and Packaging of Pakplee Districtm, Nakhon Nayok Province with the concept of design thinking. This study was a part of the King's Philosophy Project of Phranakhon Rajabhat University for the year 2021, which was an academic service project for the community along with the integration of class teaching in Communication Arts Program and Culture. It was together with the continuation of research studies on the identity of the Thai Puan community in Nakhon Nayok Province that has been done previously. This Project was a guideline to make community income.